The ultimate challenge to climate change: Endurance of a thermophilic reptile to the harsh temperatures on an extremely hot island - Melissa Plasman; Aníbal H. Díaz de la Vega-Pérez; Marshall D. McCue; Mauricio Tepos-Ramírez; Víctor Hugo Reynoso (PLoS ONE, 2025)
Herbivorous ectotherms are especially vulnerable to climate change and those inhabiting hot environments may already live near their maximum physiological limits. Insular species are particularly susceptible to changing thermal conditions because they cannot relocate. This proves a very poor prognostic for the survival of herbivorous reptiles living on islands. The piebald chuckwalla, Sauromalus varius, is a large iguana endemic to San Esteban Island, located in the Gulf of California, encompassed by the Sonoran Desert, one of the hottest areas on earth. We investigated the thermal ecology of this iguana during the hottest month of the year coinciding with the fruiting of its most important food source, the giant cardon. We measured field body temperature (Tbfield), voluntary maximum body temperature, the onset of thermal stress responses, and critical maximum temperature, and compared these with the thermal landscape. We found that Tbfield was 37.2±1.3°C (average±SD) and iguanas sought shade at a body temperature of 39.2±1.4°C. Iguanas started panting at 42.4±2.0°C, a cooling strategy at the expense of precious body water, and often defecated, at 43.2±1.9°C, with concomitant loss of water. We determined that these iguanas can maintain activity at body temperatures of 47.2±2.2°C, however they use various mechanical and behavioral mechanism to avoid these extremes. On the island, ground temperatures reached up to 62.4°C. Shade of plants can provide thermal shelter during part of the day. However, even in some caves temperatures could reach 41.5°C and under rocks 48.0°C, which is higher than these animals voluntarily tolerate. Our results indicated that although these chuckwallas can support high temperatures, their strategy incurs substantial water loss, a resource only available for the iguana through cacti consumption. Environmental temperature that increases with climate change will likely lead to an ever-increasing use of shelters, perhaps even resulting in complete inactivity during the cacti fruiting period.